Seasonal variations in microbial diversity and metabolite profiles of the gut of sea cucumber (Apostichopus japonicus) - Deng, Beini; Ru, Xiaoshang; Wang, Ting; Zhang, Chenxi; Sun, Wanhui; Lu, Songchong; Zhang, Libin (Frontiers in Marine Science, 2022)
The sea cucumber (Apostichopus japonicus) is the main economic species in China and has a significant role in aquaculture. Gut microbiome composition is closely related to external environments. In this study, we identified the effects of seasonal changes on the composition and main metabolites of symbiotic microorganisms in the intestine of A. japonicus. We used 16S rRNA sequencing to identify the composition of symbiotic microorganisms in different seasons. Intestinal metabolites were determined using liquid chromatography with tandem mass spectrometry, which linked symbiotic microorganisms to intestinal metabolites. Analyzing changes in intestinal microbial composition across different seasons. The results showed that seasonal changes of intestinal microorganisms were significant, A. japonicus were infected by Vibrio easily in summer, Stigmasterol and sitosterol could affect the growth of body wall of A. japonicus. It is vital importance for A. japonicus that the results benefit for the growth, immunity and aquaculture.